DANCE, MOVEMENT THERAPY, AND NEUROCOGNITIVE WELL-BEING - Giri, Vinodinee Vasant; Kumbhar, Uddhav T; Gautam, Jyoti; Geethapriya, Nagarajan; Kale, Swati G.; Pawar, Nilesh M (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Dance and movement therapy (DMT) has become a multidisciplinary practice that combines making use of performing arts, psychology, neuroscience, and rehabilitation science to encourage mental, emotional, and cognitive wellness. The growing number of neurological and psychological disabilities like depression, anxiety, dementia, as well as Parkinson disease have aroused enthusiasm into non-pharmacological interventions that may be used to enhance neurocognitive well-being. The simultaneous activity of several brain systems, such as motor control systems, emotion control systems, memory systems, and social cognition systems, is involved in the dance and movement activities. Dance therapy promotes neural plasticity and improves cognitive processes including attention, executive functioning and memory acquisition through body movement with rhythmic patterns, music synchrony and expression. The given research paper will provide an insight into the effectiveness of dance and movement therapy in the field of neurocognitive well-being enhancement of children, adults, and older adults. The paper examines the current literature on neurological underpinnings of the movement-based therapies, and evaluates their use in the context of mental health care, neurological rehabilitation, and community health. An overview of therapeutic models that are currently available is provided to compare their performance in terms of improving cognitive functioning and emotional stability. Moreover, in the paper, a unified neurocognitive movement therapy framework is suggested, which integrates neuroscience, creative arts therapy, and digital health monitoring technology. The results indicate that interventions based on dance are highly beneficial in enhancing psychological health, cognitive flexibility, and socialization and minimizing stress and neurological deterioration symptoms. The suggested model identifies the possibility of the interdisciplinary teamwork among neuroscientists, therapists, artists, and healthcare practitioners. The authors find that dance and movement therapy can be a useful complement to conventional medical methods of the modern society of holistic health and neurocognitive development support.